Emerging Therapies for Diabetes Mellitus: Efficacy and Safety of USFDA-Approved Drugs and Late-Stage Clinical Trials - Vaibhav Lasure; Sakshi Shankhapal; Pratiksha Sonawane; Santosh Bansode; Sachin Hodgar; Vivekanand Kashid; Pallavi Sonawane (International Journal of Toxins and Toxics, 2025)
This review provides a comprehensive analysis of drugs approved by the U.S. Food and Drug Administration (USFDA) for managing diabetes mellitus (DM) from 2013 to 2022, including emerging treatments from phase 3 clinical trials during this period. Over the past decade, the treatment landscape for diabetes has evolved significantly, with new therapies not only improving blood sugar control but also targeting broader health outcomes like heart and kidney health. In this review, we looked closely at FDA-approved drugs and also explored promising treatments still in phase 3 clinical trials—those that have shown solid results and could soon change the way diabetes is managed.We gathered information from ClinicalTrials.gov, focusing only on trials that had clear, published outcomes, to ensure our analysis was grounded in reliable data. What we found was a wide range of innovative therapies under development, each working in different ways—from targeting hormones that affect insulin release to drugs that improve how the body handles glucose. Many of these new options aim to make treatment easier, with longer-lasting effects and fewer side effects. There's also a growing trend toward combination therapies that tackle diabetes from multiple angles at once. Our study uncovers a wide range of innovative compounds in phase 3 trials, aiming at DM through diverse action mechanisms.
Keywords: Diabetes mellitus; USFDA; approved diabetes drugs; clinical trials; novel drugs